The Principal's Leadership Style in Driving a School Ecosystem and Community that Cares About Education at SDN 02 Andaleh - Dwi Suryani Alfa; Sri Wiyanti; Kamal Ruzzaman; Suswati Hendriani (CV. Bimbingan Belajar Assyfa, 2026)
The school’s initial conditions were characterized by weak relationships between the school and the surrounding community, low professionalism among some teachers, suboptimal utilization of school facilities, and inadequate character development among students. This study aimed to analyze the principal’s leadership style in building an inclusive educational ecosystem and fostering community participation in education. A qualitative approach with a single case study design was employed in a school undergoing transformative change. Data were collected through participant observation, in-depth interviews, and document analysis involving the principal, teachers, students, school committee members, and community representatives. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Trustworthiness was ensured through source and technique triangulation, member checking, and peer debriefing. The findings revealed that the principal consistently applied transformational and participatory leadership through exemplary behavior, humanistic communication, strengthening school culture, and developing partnerships with the community. This leadership contributed to improved teacher professionalism, stronger school-community relationships, better utilization of facilities, and the development of more disciplined and environmentally responsible students. The study highlights the critical role of principal leadership in achieving sustainable educational transformation.